(3QSGdI JhHjN GHf GdHQHQjI GdQSGdI GdehSheI HGdOGeZI ddaGSb hGdfLS GdaGVMI dCJHGYI Cgd GdQOIs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3HSe GdEdg GdMb hehdi GdNdb GdSdGe Ydi LeGYI GdENhGf ddeMbjf GdeJeScjf HMOhO hdi GdOjf hScGf GdMQe GdCejf s
(3BNQgG (B:s
(3abO JejRJ aQb GdcaQ hGdVdGd hHGf Cgd GdMb hGdTcQ ddhdi GdgGOi GdEeGe GdbGFe GdeWGY JeJ Hefg hdi GdCeQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B75s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3GdJhMjO hGdedd hGdfMds